Intervention in the Domestic Affairs: Questioning Definitions - V. I. Bartenev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The last decades have seen a proliferation of internationalized internal disputes and a steady growth in scholarly interest in interference in the domestic affairs of sovereign states. This bibliographic review summarizes the approaches of those scholars (predominantly from the Anglo-Saxon countries) — who focused on conceptual dimensions of the intervention problematique. The review consists of three sections. The first section examines the semantic nuances of the key terms in Russian and English languages describing interventionist behaviour and the particularities of their usage in international legal documents. The second and third sections reveal the essence of two ‘great debates’ in the literature on intervention. The first debate centers on desirability and possibility of working out a definition of intervention. The second debate focuses on delimiting semantic boundaries of the ‘intervention’ concept. The first debate is presented as a polemic between scholars who take intervention for granted, the proponents of treating it as a scientific concept and those who refuse to search for a common definition as such. The conclusion contains a critique of argumentation of those scholars — predominantly constructivists and poststructuralists — who question the possibility of obtaining a purely scientific knowledge about intervention and call for studying discourse instead, including the discourse of actors conducting interventionist actions. The author of the review justifies the need to formulate the working definition of intervention which would allow to get out of a trap conflicting perceptions in the times of an increasing interstate confrontation, revival of an ideological competition and widening divergences in conceptualisation of sovereignty, its boundaries and conditions of their violation. He also advocates for the utilization of the broadest interpretation of intervention which, on the one hand, would include both military and non-military tools (such as foreign aid, sanctions, information influence etc.), and, on the other hand, would be applicable to studying interventionist practices of different historical epochs, including the pre-Westphalian era. The review concludes with a reminder that the use of any extant definition or a development of a new one is only the first step towards a typology of interventionist actions which should be based on the study of empirical data and not on the a priori chosen parameters.